RSA: Dagli anni '70 al giorno d'oggi - Pellegrini, S (Atti della Accademia Peloritana dei Pericolanti : Classe di Scienze Fisiche, Matematiche e Naturali, 2006)
In this note, after a brief historical excursus, we describe the revolution in cryptography of the 70es, due to the introduction of public key cryptography and the RSA algorithm. We also consider some contemporary applications of this algorithm. Modern cryptography has indeed become a commodity technology, which is currently used for applications ranging from e-commerce to digital television.